2013
DOI: 10.1088/1367-2630/15/4/043049
|View full text |Cite
|
Sign up to set email alerts
|

A tunable metamaterial absorber using varactor diodes

Abstract: We present the design, analysis and measurements of a polarizationinsensitive tunable metamaterial absorber with varactor diodes embedded between metamaterial units. The basic unit shows excellent absorptivity in the designed frequency band over a wide range of incident angles. By regulating the reverse bias voltage on the varactor diode, the absorption frequency of the designed unit can be controlled continuously. The absorption mechanism is interpreted using the electromagnetic-wave interference theory. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
185
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(188 citation statements)
references
References 21 publications
2
185
0
1
Order By: Relevance
“…Researchers have proposed different methods to expand the operating bandwidths of MAs [65][66][67][68][69], while the flexible control of the MAs is still an intractable issue. Recent reports have shown that the absorbing frequencies of MAs can be dynamically adjusted by integrating tunable media (e.g., varactor diodes [70], liquid crystals [71], graphene [72], or phase-change materials [73]) to the traditional passive MAs. In some specific designs, researchers have advised to use oxide films [74] or film-cou pled colloidal nanoantennas [75] as superstrate/substrate to adjust the absorbing frequencies.…”
Section: Demonstrations For Ferrite-based Tunable Metamaterials Absorbersmentioning
confidence: 99%
“…Researchers have proposed different methods to expand the operating bandwidths of MAs [65][66][67][68][69], while the flexible control of the MAs is still an intractable issue. Recent reports have shown that the absorbing frequencies of MAs can be dynamically adjusted by integrating tunable media (e.g., varactor diodes [70], liquid crystals [71], graphene [72], or phase-change materials [73]) to the traditional passive MAs. In some specific designs, researchers have advised to use oxide films [74] or film-cou pled colloidal nanoantennas [75] as superstrate/substrate to adjust the absorbing frequencies.…”
Section: Demonstrations For Ferrite-based Tunable Metamaterials Absorbersmentioning
confidence: 99%
“…하지만 동작 주파수를 높이기 위해선 표면에 매우 작은 커패시턴스 값이 요구되는데, 상용 버랙터의 커패시턴스는 매우 크기 때문에, 주파수 가변 가능 범위가 제한된다 [5] . 입력 임피던스(Z in )는 표면 임피던스(Z surf )와 기판 임피 던스(Zsub)의 병렬연결로 표현할 수 있다 [3] .…”
Section: Fss(frequency Selective Surface)와 His(high-impedanceunclassified
“…In this method, active devices such as varactor diodes, PIN diodes and micro-electro-mechanical systems (MEMS) have been used to achieve reconfigurability. A varactor diode is extensively studied in the literature [13][14][15]. It is modeled as a variable capacitance and this property brings various advantages such as simple integration and bias distribution due to using only one diode to achieve the tuning.…”
Section: Introductionmentioning
confidence: 99%